Path Analysis on the Determinants of Adherence to Anti Tuberculosis Drug Treatment in Kaur District, Bengkulu, Indonesia - Surahman Hamidi; Setyo Sri Raharjo; Mahendra Wijaya (Masters Program in Public Health, 2019)
Background: Drug treatment compliance was the behavior of patients to take medication and undergo treatment according to the rules determined by professional health personnels. Many factors influenced the compliance with treatment for tuberculosis patients. This study aimed to examine determinants of drug treatment compliance among tuberculosis patients.Subjects and Method: This was an analytic observational study with a cross-sectional design. The study was conducted at 16 community health centers in Kaur Regency, Bengkulu, Indonesia, from January to February 2019. A sample of 206 study subjects was selected by purposive sampling. The dependent variable was drug treatment adherence. The indepen